EXPLORING THE RELATIONSHIP BETWEEN BOOST IN TOLERANCE, NEED TO BELONG, AND LIFE SATISFACTION AMONG UNDERGRADUATE UNIVERSITY STUDENTS - Hayat Muhammad; Basharat Hussain; Zabih Ullah (Journal of Religion and Society, 2025)
The study examines the relationships between Boost in Tolerance, Need to Belong, and Satisfaction in Life among undergraduate university students. A total of 576 students (M = 21 years) from various faculties and departments participated in the study, with an equal number of male and female respondents. Using a purposive sampling technique, participants completed three validated scales: the Tolerance for Disagreement Scale, the Need to Belong Scale, and the Satisfaction with Life Scale (SWL). Results revealed a weak but statistically significant positive correlation between Boost in Tolerance and Need to Belong (r = 0.22, p < 0.01). This suggests that individuals with higher tolerance levels tend to experience a slightly greater need for social inclusion. A moderate positive correlation was observed between Boost in Tolerance and Satisfaction in Life (r = 0.36, p < 0.01), indicating that increased tolerance is associated with improved well-being. However, the correlation between Need to Belong and Satisfaction in Life was weak (r = 0.08, p < 0.05), suggesting minimal practical significance. Additionally, a t-test analysis of gender differences found no significant variation in Boost in Tolerance (t = 0.49, p = 0.31) or Satisfaction in Life (t = 1.52, p = 0.06). A significant gender difference was found between males and females on Need to Belong (t = -2.7, p < 0.001), with females reporting a higher need for belonging. The findings will help understand the interplay between satisfaction in life, the need for belonging and a boost in tolerance in university students. Keywords: Tolerance, Need to Belong, Life Satisfaction, Undergraduate Students, Well-Being